The choice of the forms of Lyapunov functions for a positive 2D Roesser model - Kaczorek, Tadeusz (1932- ) (Zielona Góra: Uniwersytet Zielonogórski)
The appropriate choice of the forms of Lyapunov functions for a positive 2D Roesser model is addressed.
Keywords: Lyapunov function; positive 2D Roesser model; asymptotic stability